Spectrophotometric Estimation of Tramadol Hydrochloride in Pharmaceutical Dosage Forms - Singh Rathore, Garvendra; K. Basniwal, Pawan; Suthar, Manish; N. Gupta, Roop. (Asian Journal of Chemistry, 2010)
Two rapid, simple, precise and economical methods viz., linear regression equation and standard absorptivity were developed and validated for estimation of tramadol hydrochloride in pharmaceutical dosage forms. The estimation of tramadol hydrochloride was carried out at 271 nm. Beer-Lamberts law was obeyed in the concentration range of 50-250 μg/mL and standard absorptivity A (1 %, 1 cm) was found to be 58.95 dl g-1 cm-1. The molar extinction coefficient (ε) for the drug was found to be 1767.61 mol-1 cm-1. Both methods were validated for linearity, accuracy, precision and robustness. The numerical value for all validation parameters lies within the acceptable limits.